Ideology, Family Policy, Production, and (Re)Education: Literary Treatment of Abortion in the GDR of the Early 1980s - Heinz Bulmahn (Studies in 20th & 21st Century Literature, 1997)
The decision by the Constitutional Court in Karlsruhe of placing restrictions on the right to an abortion will profoundly affect German women's right to choose. This decision is a culmination of efforts to errode the right to choose for West as well as East German women. In the former GDR, even though liberal abortion laws allowed women access to free abortions, for ideological reasons, the government devised policies that discouraged abortions as a means of birth control. This policy becomes particularly apparent in the early 1980s when the East German government, confronted with a declining birth rate, faced the dilemma of how to leave the existing liberal abortion law intact while discouraging women from aborting their fetuses. To accomplish this task officials persuaded writers to produce literary works that promoted a three-child family policy where abortion was relegated to an inappropriate option. The article analyzes several literary works written in the early 1980s within the context of this renewed effort to encourage women to produce more children at the expense of their personal choice, and concludes that, in spite of the liberal abortion rights in the former GDR, the conditions for exercising these rights proved to be far less favorable.
Keywords: Constitutional Court; Karlsruhe; right to an abortion; abortion; Germany; German women& #x27; s right to choose; Early 1980s; GDR; Family Policy; liberal abortion laws; free abortion; ideological reasons; discouraged; birth control; East German government; DDR; declining birth rate; fetuses; literary works; promoted; three-child family policy; inappropriate; women; children; personal choice; former GDR